A new species of Evonima Walker, 1865 (Lepidoptera: Nolidae: Nolinae) from China - Hu, Yanqing; László, Gyula M.; Ronkay, Gábor; Wang, Min (Zootaxa, 2013)
The genus Evonima Walker, 1865 was established with the type species aperta Walker, 1865. Evonima as currently understood is a species-rich genus having rather variable forewing pattern, with a South-East Asian and African geographic distribution (see Hacker et al. 2012). The known species of Evonima are separable by external features; although the genus as a whole displays distinctive genitalia, the individual species are similar genitalically. Evonima contains 12 South-East Asian species: E. aperta Walker, 1865, E. xanthoplaga (Hampson, 1911), E. ochritincta (Hampson, 1901), E. unicolor László, Ronkay & Witt, 2010, E. faircloughi Holloway, 2003, E. kamboranga Holloway, 2003, E. maculata Holloway, 2003, E. mandschuriana (Oberthür, 1880), E. elegans Inoue, 1991, E. minora (Eecke, 1926), E. plagiola (Hampson, 1898) and E. albifurca (Hampson, 1914). The African fauna (see Hacker et al. 2012) contains 4 taxa: E. westafricana Hacker, 2012, E. littoralis littoralis (van Son, 1933), E. littoralis abyssinica Hacker, 2012 and E. ruhija Hacker, 2012. It is worth noting that, of these, only E. westafricana actually belongs within Evonima; the other African species mentioned by them are representatives of closely related but distinct genera, despite their external similarity with Evonima species; the configuration of their male genitalia clearly show their distinctness from Evonima. In our recent survey of the Chinese Nolinae, we found a striking new Evonima species, which we describe herein.